Realtime parameter estimation, calibration and simulation of a DC motor - (:unkn) unknown (DRUNPP-SARAJEVO, 2011)
This paper is about real time estimation and calibration of a brushed wound-pole dc motor parameters, experimantally. An Electrical Machines Test Bed (EMTB), a dc motor with a driver and a data acquisition card (DAQ) installed computer is used in the experiment setup. The software application is developed on Matlab-Simulink platform using Real-Time Windows Target library. Firstly, motor parameters are estimated by using ODEs. Then estimated parameters are simulated within the model and compared with real motor behaviour. Finally, parameters are calibrated with Mat lab-Parameter Estimation tool and linear model of the dc motor is acquired according to velocity output.
Keywords: parameter estimation; parameter calibration; simulation; modeling; model validation; IDENTIFICATION